A Detection of Distributed Denial of Service Attack Using Advanced Quadratic Route Factor Estimation - K Abdul Basith, Dr. T. N. Shankar (International Journal of Advanced Science and Technology, 2020)
Denial-of-Service (DoS) attacks, mainly distributed DoS (DDoS) attacks have become essential and growing threats to the online. Massive forces from both academia and enterprise have performed on the detection and protection of DDoS attacks. But, most detection and protection systems do not straight aim at defending the victim of attacks itself but attack sources or standard network units.However, this part has not discussed enough in the literature. There are various Detection methods introduced in the research. But their work has a limitation in sensor power, computation, and communication capacities. Our goal is to produce defense mechanisms to detect the attacks generated by the malicious node. To solve these difficulties and to increase the security of attack prediction, it is essential to provide Enhanced detection mechanisms that can control the Exhaustion attack and Denial of Service attack. In this paper, Advanced Quadratic Route Factor (AQRF) Estimation method suggested in a wireless ad hoc network, and this model is introduced to detect and mitigate the routing attacks. In which it keeps route details and network information at every time frame based on various quarters of the geographic network area. This method divides the region of the whole network into four parts, and for each quadratic region, a time-based snap and route information are stored. The distributed detection of routing attack increases the performance of the network and improves the Detection accuracy also. Similarly, for the detection of routing attacks, the method uses the snapshot and route traces with the help of packet information.The experimental results compare with previous attack detection methods of Watchdog and SVM. The proposed system has a high detection efficiency, the detection rate of it could reach more than 97%.